Robust Nonlinear Disturbance Observer Based Adaptive Guidance Law Against Uncertainties in Missile Dynamics and Target Maneuver - Chwa, Dongkyoung (IEEE Transactions on Aerospace and Electronic Systems, 2018)
The proposed robust nonlinear disturbance observer based adaptive guidance method considers the nonlinear coupled missile dynamics and rapidly maneuvering target. It also includes unavailable information such as high-order line-of-sight rates and target acceleration as time-varying parametric uncertainties and nonparametric disturbances. An integrated guidance and control model, a robust nonlinear disturbance observer, a nonlinear missile jerk observer, and a robust nonlinear guidance law are proposed, the validity of which is demonstrated by stability analysis and simulations.
Keywords: Disturbance observer; Integrated guidance and controls; Non-linear missile; Non-parametric; Nonlinear disturbance observer; Nonlinear guidance laws; Uncertainty; Integrated guidance and control model; nonlinear missile jerk observer; parametric uncertainties and nonparametric disturbances; robust nonlinear disturbance observer; robust nonlinear guidance law